1991
DOI: 10.1103/physrevlett.66.2243
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic electron accumulation layers on reconstructed clean InAs(100) surfaces

Abstract: The electronic structures of clean InAs(lOO) surfaces have been investigated by in situ high-resolution electron-energy-loss spectroscopy. Intrinsic electron accumulation layers with carrier densities strongly depending on the surface reconstruction are formed on both As-stabilized and In-stabilized surfaces. The correlation between the surface electron densities and the surface reconstructions suggests that electrons in the accumulation layers are induced by the donorlike intrinsic surface states of InAs whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
203
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(223 citation statements)
references
References 16 publications
18
203
1
1
Order By: Relevance
“…Mobilities and densities vary per sample, yet no significantly systematic variation caused by solution coverage is observed. The values of n s are consistent with previous studies 14,15 . The assignation is confirmed by a self-consistent calculation, using non-parabolicity in the InAs dispersion, with a Γ-point effective mass of 0.024 and low T band gap of 418 meV.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Mobilities and densities vary per sample, yet no significantly systematic variation caused by solution coverage is observed. The values of n s are consistent with previous studies 14,15 . The assignation is confirmed by a self-consistent calculation, using non-parabolicity in the InAs dispersion, with a Γ-point effective mass of 0.024 and low T band gap of 418 meV.…”
supporting
confidence: 82%
“…To extract values for τ s it is advantageous to use a system with pre-existing prominent SOI because the characteristic magnetoresistance of AL shows a turnaround from positive to negative magnetoresistance under increasing B, fa- cilitating unique numerical fits of the AL model to the data. It is well established that at the surfaces of InAs the Fermi level E F is pinned above the conduction band, forming a surface electron accumulation layer and hence a two-dimensional electron system (2DES) at the surface [12][13][14][15] . Our experiments require electrons in close proximity to the local moments, satisfied by the InAs surface 2DES.…”
mentioning
confidence: 99%
“…These study results also could be illustrated by surface band bending, as shown in Figure 2b. InAs has been found to have accumulated electrons on surface and causes downward surface band bending 76, 77, 78. For InAs NW with limited diameter, when under photoexcitation, photogenerated electrons move to the surface and are trapped whereas holes are left in the core and recombine with free electrons, leading to the NPC.…”
Section: Trap‐ and Hybrid‐induced Photogatingmentioning
confidence: 99%
“…In addition, the accumulated carrier density depends upon whether the surface is As-stabilized or In-stabilized. 20 At light doping, the accumulation layer becomes distinctly localized near the surface, while, at heavy doping, the accumulation only means that the carrier density in the semi-infinite system becomes enhanced in the neighborhood of the surface. With further increase in doping level, there occurs no substantial accumulation at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are some other EELS measurements on an intrinsic accumulation layer at a clean n-type InAs ͑001͒ surface prepared carefully. 19,20 At light doping, quasi-two-dimensional plasmons occur in a sharply localized accumulation layer, 20 while, at heavy doping, electronic excitations in the accumulation layer are virtually surface plasmons in a semi-infinite system with the carrier density enhanced near the surface. 19 In relation to the EELS measurements, the surface excitations in the absence and the presence of a surface spacecharge layer have been calculated by means of a hydrodynamic theory combined with a step density-profile model, 19,28,29 a semiclassical local-response theory formulated in Ref.…”
Section: Introductionmentioning
confidence: 99%